Uji Daya Hambat Kombinasi Ekstrak Daun Nanas (Ananas Comosus (L.) Merr.) Dan Daun Sirih Hijau (Piper Betle L.) Terhadap Bakteri Propionibacterium Acnes Dan Staphylococcus Aureus - Layla Zuhra; Yolanda Eliza Putri Lubis; Suandy Suandy (Riviera Publishing, 2025)
Acne vulgaris is a chronic inflammatory condition of the pilosebaceous glands characterized by various types of lesions, commonly affecting adolescents and young adults. Among the principal causative bacteria are Propionibacterium acnes and Staphylococcus aureus. Conventional topical antibiotic therapy may lead to side effects such as skin irritation and antibiotic resistance, which points to the importance of alternative antimicrobial agents sourced from natural products. This experimental study aimed to evaluate the antibacterial activity of a combination of ethanol extracts of pineapple leaves (Ananas comosus (L.) Merr.) and green betel leaves (Piper betle L.) against P. acnes and S. aureus. The extracts were prepared using the maceration method with 96% ethanol and tested at concentrations of 20%, 40%, and 60%. Antibacterial activity was determined by the disk diffusion method (Kirby-Bauer) on Nutrient Agar, using clindamycin as the positive control and sterile aquadest as the negative control. The results demonstrated that all concentrations of the extract combination produced inhibition zones against P. acnes (mean diameters: 20.23 mm, 22.69 mm, and 24.85 mm) and S. aureus (mean diameters: 20.51 mm, 20.23 mm, and 24.74 mm), with the greatest effects observed at 60% concentration. Statistical analysis indicated a significant difference in inhibition against P. acnes (p = 0.016), but not against S. aureus. These findings support the potential use of pineapple and green betel leaf extract combinations as alternative topical antibacterial agents for acne treatment, particularly against P. acnes, and warrant further research into their use as natural anti-acne formulations.